ANALISIS BEBAN OPERASIONAL DAN PENDAPATAN OPERASIONAL TERHADAP LABA BERSIH PADA PT BPR SATYA MITRA ANDALAN BATAM - Melisa; Dian Lestari Siregar (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The purpose of this study was to determine whether operating expenses andoperating income had an effect on net income at PT BPR Satya Mitra Andalan.In this study, researchers used descriptive research methods. The population inthis study is the income statement at PT BPR Satya Mitra Andalan Batam for thelast five years. The sample used in this research is purposive samplingtechnique. The type of data in this study is quantitative data and the data sourceused is secondary data. The technique of collecting data in this research isdocumentation. The data analysis technique used for this research is theStatistical Package Of Social Sciences (SPSS). Based on the results of theresearch on Operating Expenses and Operating Income on Net Profit, Fcount325,310 > Ftable 3.59 and Sig. of 0.000 < 0.05. This means that H0 is rejectedand H3 is accepted. So it can be concluded that simultaneously OperatingExpenses and Operating Income have a significant effect on Net Profit at PTBPR Satya Mitra Andalan.